ARTIFICIAL INTELLIGENCE AND ITS ROLE IN MODERN SOCIETY - Jalolov Tursunbek Sadriddinovich; Maxdiyeva Manzura Muxiddinovna (Recent scientific discoveries and methodological research, 2025)
This article analyzes the concept of artificial intelligence (AI), its stages of development, main technologies, areas of application, positive and negative impact on society, as well as its role in the future. AI is currently actively implemented in many areas, such as education, medicine, industry, finance, transport, security, and is fundamentally changing the way of life of mankind. The article is intended for students studying in the IT field, specialists engaged in AI technologies, and general readers.